2022
DOI: 10.54996/anatolianjem.1008029
|View full text |Cite
|
Sign up to set email alerts
|

Response Times of Emergency Medical Services in Ankara over the Last Five Years

Abstract: Aim: Emergency medical services (EMS) must be delivered continuously and quickly in order to treat patients as soon as possible. The purpose of this study was to assess the activities and response times of the EMS in Ankara over the last five years.Material and Methods: Database of the Ministry of Health, Emergency Health Automation System (ASOS), was used to obtain data for the past five years (01.01.2015 -31.12.2019). Reasons and outcomes of the calls, response times, and the number of EMS personnel and ambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In the study conducted by Vuorinen et al, the time spent in EMS was found to be 99 minutes (14). In a local study conducted in the region where our study was conducted, the EMS arrival time to the patient was reported to be 6 minutes 12 seconds in 2019 (15). We found this time to be 40 minutes.…”
Section: Discussionsupporting
confidence: 44%
“…In the study conducted by Vuorinen et al, the time spent in EMS was found to be 99 minutes (14). In a local study conducted in the region where our study was conducted, the EMS arrival time to the patient was reported to be 6 minutes 12 seconds in 2019 (15). We found this time to be 40 minutes.…”
Section: Discussionsupporting
confidence: 44%